Motion Preserving Surgery Using O-Arm for Unstable Hangman Fracture - Verma, Satish Kumar; Singh, Pankaj Kumar; Sawarkar, Dattaraj Parmanand; Kumar, Amandeep; Agarwal, Deepak; Chandra, P. Sarat; Kale, Shashank Sharad (Indian Journal of Neurotrauma, 2019)
Aim To evaluate clinical outcomes, radiological findings (displacement and angulation), and bony fusion in cases of unstable hangman’s fracture.Introduction Hangman fracture, also known as traumatic spondylolisthesis of axis vertebra, is classically defined as bilateral pars interarticularis fracture of axis vertebra. Opinions vary regarding optimal treatment of unstable hangman’s fractures. Some authors have recommended use of rigid orthosis, whereas others have recommended internal fixation. The peculiar anatomy of the upper cervical spine is highly variable, and presence of surrounding neurovascular structures makes axis pedicle screw fixation even more technically challenging. The advent of intraoperative three-dimensional navigation systems facilitates safe and accurate instrumentation.Materials and Methods This article analyzes patients operated for type II and IIa hangman’s fractures during the period from September 2011 to August 2018 by two neurosurgeons. The patients’ age, sex, mechanism of injury, associated injuries, and neurologic status were noted. The authors retrospectively assessed the clinical outcome, radiological findings (displacement and angulation), and bony fusion.Result Eighteen patients with age ranging from 17 to 81 years, were operated using computed tomography-based (O-arm) navigation. Accuracy of screw insertion, preoperative and postoperative displacement, and angulation of C2 over C3 were evaluated. Bony fusion was assessed in all patients. A total of 92 screws were inserted: 36 screws in C2 pedicle, 34 in C3 lateral mass, 20 in C4 lateral mass, and 2 in C5 lateral mass. Of these 92 screws, 36 C2 pedicle screws were inserted under O-arm guidance. The mean preoperative C2–C3 displacement was 4.5 ± 2.1 mm, and the mean postoperative displacement was 1.8 ± 1.1 mm with a mean reduction of 2.7 ± 1.4 mm. The mean preoperative C2–C3 angulation was 10.2 ± 7.6 degrees and the postoperative angulation was 2.52 ± 4.62 degrees with a mean reduction of 8.2 ± 11.6 degrees. Screw malplacement was seen in two C2 pedicle screws (2/36, 5.5%). All C2 pedicle screw breaches were of grade 2. Excellent anatomical reduction in all cases could be achieved as established by the improvement in morphological parameters of fracture.Conclusion This series using O-arm in unstable hangman fracture demonstrates that intraoperative O-arm-based navigation is a safe, accurate, and effective tool for screw placement in patients with unstable hangman fracture.
Keywords: axis vertebra; hangman fracture; instrumentation; intraoperative navigation; pedicle screw